Investment and Enconomic Indicators in Malaysia / Masturah Ma’in, Norfaiezah Nordin, Izza Hazira Zailan, Saliza Sulaiman, Zuraidah Ismail - Ma’in, Masturah; Nordin, Norfaiezah; Zailan, Izza Hazira; Sulaiman, Saliza; Ismail, Zuraidah (Faculty of Business and Management ; UiTM Press, 2018)
This study is to investigate the relationship between economic indicators and investment in Malaysia using secondary data spanned through 1982-2015. This study employs an empirical analysis by adapting the unit root test, Johansen co-integration test and vector error correction model (VECM) to determine the short-run and long run effect among variables. The cointegrating test indicates that investment is significantly related to the trade openness, GDP and population. Based on the VECM results, the findings show that a long run relationship exists between the trade openness and investment in Malaysia. Hence, these reveal that it is important for the Malaysian government to enhance the economic policy in liberalizing foreign trade in order to encourage more investments.